Political Zionism from the Basel Conference to the Balfour Declaration 1897 ـ 1917 - Emhammed, Emhammed Ibrahim (Al-Mukhtar Journal of Social Sciences, 2011)
The study explores the political aspects of Zionism from the Basel Conference to the Balfour Declaration. The document provides an analysis of historical events and key milestones related to the development of political Zionism. It covers topics such as the significance of the Basel Conference in 1897, the issuance of the Balfour Declaration in 1917, and the subsequent impact on the Zionist movement. The study also discusses the historical context surrounding these events, including the political landscape of the time. Overall, this research serves as a comprehensive resource for understanding the political dimensions of Zionism in the period leading up to the Balfour Declaration.